A linear cavity S-band Brillouin/Erbium fiber laser - Harun, S. W.; Zulkifli, M. Z.; Ahmad, H. (2006)
A linear cavity short wavelength band Brillouin/Erbium fiber laser (S-band BEFL) is demonstrated. The architecture utilizes a bi-directional oscillation provided by two optical circulators at both ends of the laser cavity. Therefore, the number of channel is higher in this BEFL compared with the ring-based S-band BEFL. A stable output laser comb with 11 channels was obtained with Brillouin and 980 nm pumps of 9.4 mW and 206.5 mW, respectively at around 1503 nm region. The BEFL has the potential to be used in the future dense wave-length division multiplexing communication system.